Pengaruh Perspektif Gender Terhadap Keputusan Transaksi Saham - M Iqbal Harori; Kussuyatmono Bagus Wardianto; Suripto S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The research aims to analyze the effect of gender and other dominant factors in stock transaction decisions. The research was conducted in Lampung Province. This type of research uses a quantitative approach and multiple linear regression, using primary and secondary data derived from questionnaires using a Likert scale. The gender analysis was carried out using the HARVARD method. The results of the study show that education, employment and income are still dominated by male investors. However, women are more able to be careful in making decisions compared to men. There are also more female investors who can make decisions more accurately than men. These symptoms indicate that female investors are more optimal in utilizing existing information. Then there is overconfidence bias and optimism bias in making stock investment decisions for investors in Lampung, which has the potential for mistakes in making decisions and causing investors to increase the intensity and amount of investment and to be more courageous in taking investment risks.